The Contribution of Legs Muscle Power and Dynamic Balance Toward Jump Shot Ability on Senior High School Basketball Players in Padang - Fahd Mukhtarsyaf; Aldo Naza Putra Aldo (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
The purpose of this study is to find out the contribution magnitude of legs muscle power and dynamic balance to the ability of jump shot Senior High School Basketball players in Padang. Based on the problem, this research method using correlational approach and followed by analyzing the magnitude of contribution of each indicator variable to the predictor variable. To measure the legs muscle power using Sargeant test, dynamic balance using modified Bass Test, and for jump shot ability using speed spot shooting test. The sample involved in this study is 30 people which determined by training experience and frequency of participation in the competitions. The results of this research shows that legs muscle power contributed 22% toward the ability of jump shot; dynamic balance contributes 20% toward the ability of jump shot; and legs muscle power along with dynamic balance contributes significantly to 24% toward jump shot ability. Based on data analysis, it is concluded that the power of legs muscle and dynamic balance must be considered to be included into the training program especially to improve the ability of jump shot of Senior High School Basketball players in Padang.